A study on the impact of innovative technologies in the hospitality industry / Edgar D’Souza and Kevin D’Souza - D’Souza, Edgar; D’Souza, Kevin (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
As hotels strive to compete for business, technology adoption is critical to enhance the guest experience. In the last decade, we have seen some innovative trends take shape in the hospitality industry. The objective of this study is to assess the impact of technology-based innovations on hotel customer experiences, using a framework of four types of innovation. The study aims to determine which types of innovation are most important to guests, as well as how the value of innovative technology may vary based on demographic factors and trip intent. By achieving this objective, the study seeks to provide insights into how hotels can use technology to enhance guest satisfaction and loyalty. An analysis of popular hotel websites, discussions with hotel managers, and an internet search for the latest technologydriven innovations in hotels were all part of the qualitative phase. A questionnaire for hotel guests was constructed in the quantitative stage, yielding a sample of 631 valid completed questionnaires. Considering a framework that includes four types of innovation (i.e., product innovations, process innovations, enhanced knowledge of the market, and management innovations), this paper examines the impact of existing innovative technologies adopted by hotels on customer experiences and evaluates its potential for improving their stay. This research explores technological innovations perceived by respondents as the five most important technologies to enhance their hotel experience. Based on the four-category typology, the innovations that the guest felt like the most important were process innovations followed by product innovations. Overall, the findings suggest that hoteliers need to keep up with technological advancements to maintain and acquire new guests, but also need to consider differences in guests' wants, needs, and travel patterns.